2011
DOI: 10.1002/cncr.26164
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of complementary medicine use in a phase 1 clinical trials program

Abstract: BACKGROUND: A key end point of early cancer clinical trials is the assessment of toxicities and their possible association with new experimental drugs. Therefore, the concurrent use of complementary and alternative medicine (CAM) in patients with advanced malignancies seen in a dedicated phase 1 clinic was evaluated. METHODS: An investigator‐designed survey was anonymously completed by patients seen in the phase 1 clinic. Pharmacologic CAM included any oral, topical, or intravenous agent, including vitamins, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 18 publications
2
49
2
Order By: Relevance
“…Therefore, it was necessary to use a nonanonymous questionnaire to be able to perform a review of the corresponding chart. In contrast to higher rates in the literature with about 30-60% of the oncology patients using CAM [1][2][3][4][5][6][7][8] , we found CAM use only in 30% (271/904) of the patient sample. This may be partly due to our restrictive CAM definition excluding other CAM methods such as mind-body interventions (e.g., breathing techniques, meditation, relaxation, yoga, tai chi, qigong, cognitive-behavioral therapies, autogenic training, hypnosis, or biofeedback) and alternative medical systems (including acupuncture, moxibustion, and acupressure), but may also be a limitation of our survey, if patients do not fully disclose their CAM therapies in a nonanonymous questionnaire.…”
Section: Discussioncontrasting
confidence: 54%
“…Therefore, it was necessary to use a nonanonymous questionnaire to be able to perform a review of the corresponding chart. In contrast to higher rates in the literature with about 30-60% of the oncology patients using CAM [1][2][3][4][5][6][7][8] , we found CAM use only in 30% (271/904) of the patient sample. This may be partly due to our restrictive CAM definition excluding other CAM methods such as mind-body interventions (e.g., breathing techniques, meditation, relaxation, yoga, tai chi, qigong, cognitive-behavioral therapies, autogenic training, hypnosis, or biofeedback) and alternative medical systems (including acupuncture, moxibustion, and acupressure), but may also be a limitation of our survey, if patients do not fully disclose their CAM therapies in a nonanonymous questionnaire.…”
Section: Discussioncontrasting
confidence: 54%
“…Whereas in the literature disclosure to a physician is normally low [14,15,16,17,18], nearly two thirds of the participants in our survey said they had informed a physician. General practitioners were more often informed than specialists and oncologists.…”
Section: Discussionmentioning
confidence: 88%
“…Family members and friends as well as the mass media are the most frequently chosen sources of information about CAM. Research has shown that the majority of patients do not discuss their CAM use with their oncologist [14,15,16,17,18]. The most prominent problem of these sources of information is their low or unknown quality concerning evidence and reliability [19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis indicated an increase in TCAM use for patients with cancer from an estimated 25% in the 1970s and 1980s to more than 32% in the 1990s and to 49% after 2000 (6). Data from recent studies have indicated that the rate of TCAM use is 77% or even higher (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%